Instructıonal resources for teachıng bıology ın secondary schools ın Moro, Kwara State-Nigeria - Florence Omosholape Abidoye; Maroof Zanab Aliyu; Aduke Rihanat Ahmed; Ogunlowo Simeon Oluwole (University of Muhammadiyah Malang, 2022)
Instructional resources play an important role in conducting high quality education. This research assessed the availability and utilization of instructional resources in Moro Local Government Area (LGA) of Kwara State, Nigeria. Descriptive survey research was adopted for the study. A total of sixty (60) Biology teachers were randomly sampled from eighteen (18) schools in Moro Local Government Area Kwara State. Three research questions and two hypotheses guided this study. Questionnaire was used as an instrument for data collection and the data was analysed using simple percentage, ANOVA and t-test. The results of the study revealed that instructional resources for teaching Biology were not available in most senior secondary schools in Moro LGA of Kwara State. As high as 51% Biology teachers’ ultilized available instructional resources. Teachers’ academic qualification significantly influences their use of instructional resources for teaching Biology and there was no significant influence of school type in the use of instructional resources in teaching Biology. Recommendations made were that the government should provide more equipment for the schools for effective teaching and learning Biology, teachers should be encouraged to use Biology laboratory equipment, and in-service teachers training should be encouraged to improve their qualification.